Elbow hemiarthroplasty with a 3D-printed prosthesis for distal humeral bone defects after tumor excision: a case report - Yingkang Zhu; Shuo Gong; Jin Dai; Lei Zhou (3D Printing in Medicine, 2023)
Abstract Introduction The distal humerus is a rare site for primary and metastatic bone tumors. Due to the scarcity of cases and lack of standardized surgical strategies, it is often difficult for surgeons to choose the right choice. The application of a 3D-printed prosthesis with hemiarthroplasty for the treatment of the distal humerus after tumor resection can be a very effective option. Case presentation We present a clinical case of a 3D-printed distal humeral prosthesis for the treatment of bone defects caused by metastatic bone tumors. The preoperative evaluation was aggressively performed, and the decision was made to distal humeral hemiarthroplasty (DHH) after wide resection of the tumor segment bone. Processing of the Digital Imaging and Communications in Medicine (DICOM) data from CT scans performed after mirror conversion using CT data of the contralateral humerus, we designed a 3D-printed distal humeral prosthesis with hemiarthroplasty. After reconstruction of bone and surrounding soft tissue by the 3D-printed prosthesis combined with the LARS ligament and regular follow-up for 12 months, the patient had an MSTS-93 score of 29 and an MEP of 100, which reached a good level, and the patient was fully competent in normal daily activities. Conclusions Our results show that the 3D-printed modular prosthesis with hemiarthroplasty is a very effective option for cases of large elbow bone defects due to primary bone tumors or metastatic disease. However, careful preoperative preparation is required for the best outcome. Careful preoperative preparation and long-term follow-up are essential for the best outcome.